ТҮРІК ТІЛІНДЕГІ КӨПМАҒЫНАЛЫ ЭТИКЕТ ТІЛДІК БІРЛІКТЕР (ҚазҰУ хабаршысы. Шығыстану сериясы, 2016)
In the article it is considered the forms and usage of multisemantic etiquette Linguistical units with their examples.